2020
DOI: 10.1002/lary.28645
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Strength and Voice Quality as Outcome of Levodopa Challenge Test in Parkinson Disease

Abstract: Objective: To assess the usefulness of orofacial strength and voice quality as assessment of response to levodopa challenge test (LCT) used in the diagnosis of early idiopathic Parkinson disease (IPD). Study Design: Controlled Prospective Study. Methods: From January 2014 to April 2019, patients with early IPD and healthy individuals were recruited and evaluated for clinical findings (Hoehn and Yahr scale; Unified Parkinson's Disease Rating Scale); Voice Handicap Index (VHI); grade of dysphonia, roughness, bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Another important finding in this study concerns the effect of L-Dopa on voice abnormalities in PD which is still a matter of debate given previous reports on beneficial ( 28 , 29 , 31 33 ) or null effect ( 27 , 30 ). We here demonstrated that L-Dopa exerts significant improvement of voice in mid-advanced-stage patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Another important finding in this study concerns the effect of L-Dopa on voice abnormalities in PD which is still a matter of debate given previous reports on beneficial ( 28 , 29 , 31 33 ) or null effect ( 27 , 30 ). We here demonstrated that L-Dopa exerts significant improvement of voice in mid-advanced-stage patients.…”
Section: Discussionmentioning
confidence: 83%
“…Also, it is relevant to verify whether machine learning can recognize the effect of disease severity by discriminating patients in different stages of the disease. Still, given that the symptomatic effect of L-Dopa on voice is still largely a matter of debate (1,10,(27)(28)(29)(30)(31)(32)(33), it is relevant to compare the instrumental voice analysis with machine learning in patients under and not under L-Dopa treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This clinical variability of voice and speech features corresponds to the diversity of the disease 41 and its subtypes, from the early to the latter stages, and is to a certain extent affected by an important variation in cognitive impairment 42,43 . This heterogeneity may also correspond to the lack of a specific assessment method for voice and language in PD patients with DBS and to “a lack of standardization of acoustic measurement methods” as highlighted by Lechien et al 44 or to the examining physician's experience 41 . Some authors have argued that PD patients with subthalamic DBS have vocal characteristics that might be clustered: patients under stimulation present a persistent worsening of preexisting hypokinetic dysarthria in 1 of 4 cases or develop spastic dysarthria, stammering, vocal tightness, and murmur 31 …”
Section: Discussionmentioning
confidence: 99%
“…42,43 This heterogeneity may also correspond to the lack of a specific assessment method for voice and language in PD patients with DBS and to ''a lack of standardization of acoustic measurement methods'' as highlighted by Lechien et al 44 or to the examining physician's experience. 41 Some authors have argued that PD patients with subthalamic DBS have vocal characteristics that might be clustered: patients under stimulation present a persistent worsening of preexisting hypokinetic dysarthria in 1 of 4 cases or develop spastic dysarthria, stammering, vocal tightness, and murmur. 31 A relationship has been proposed between the activation of the dentato-rubro-thalamic tract and an excessively medial positioning of the left STN stimulation electrode to explain a deterioration in fluency in patients with dominant akinetic rigid disorders 45 or between excessive ventromedial thalamic positioning to explain degradation in verbal fluency in cases of DBS at the level of the VIM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation